The The Contribution of SMEs to Global Food Security Case Study: Traditional Food - Assegaf, Safira; Rachmawati, Annisa Noor; Saputro, Hendri Gigih (Politeknik NEST, 2025)
Food security is a multifaceted issue that encompasses the availability, access, utilization, and stability of food sources necessary to maintain a healthy and active life. As defined by the Food and Agriculture Organization (FAO) of the United Nations, food security exists when all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food that meets their dietary needs and food preferences for an active and healthy life. Recent trends and studies from 2017 to 2023 have highlighted several key challenges and advancements in the realm of food security. Climate change, for example, has emerged as a significant threat, affecting agricultural productivity and food availability worldwide. This literature review delves into the role of traditional food Small and Medium Enterprises (SMEs) in enhancing food security across various regions and contexts. Through an analysis of multiple studies conducted in different countries, several key themes emerge.